An optical technique for mapping microviscosity dynamics in cellular organelles - Chambers,JE; Kubánková,M; Huber,RG; López-Duarte,I; Avezov,E; Bond,PJ; Marciniak,SJ; Kuimova,MK (ACS Nano, 2018)
Microscopic viscosity (microviscosity) is a key determinant of diffusion in the cell and defines the rate of biological processes occurring at the nanoscale, including enzyme-driven metabolism and protein folding. Here we establish a rotor-based organelle viscosity imaging (ROVI) methodology that enables real-time quantitative mapping of cell microviscosity. This approach uses environment-sensitive dyes termed molecular rotors, covalently linked to genetically encoded probes to provide compartment-specific microviscosity measurements via fluorescence lifetime imaging. ROVI visualized spatial and temporal dynamics of microviscosity with suborganellar resolution, reporting on a microviscosity difference of nearly an order of magnitude between subcellular compartments. In the mitochondrial matrix, ROVI revealed several striking findings: a broad heterogeneity of microviscosity among individual mitochondria, unparalleled resilience to osmotic stress, and real-time changes in microviscosity during mitochondrial depolarization. These findings demonstrate the use of ROVI to explore the biophysical mechanisms underlying cell biological processes.